2018
DOI: 10.1097/igc.0000000000001195
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Pathological Margin Distance and Prognostic Factors After Primary Surgery in Squamous Cell Carcinoma of the Vulva

Abstract: Our data suggest that a more than 2 mm tumor-free margins is associated with better local control. In addition, older age is an independent prognostic factor for survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…Similar results to ours were obtained in other studies [8][9][10]. Arvas et al showed that a margin ≤2 mm may increase the risk of recurrence, but was not an independent predictive factor for PFS and OS [11]. Woelber et al showed a similar rate of local recurrence in patients with a margin <8 mm vs. ≥8 mm (12.6% vs. 10.2% respectively) [12].…”
Section: Discussionsupporting
confidence: 89%
“…Similar results to ours were obtained in other studies [8][9][10]. Arvas et al showed that a margin ≤2 mm may increase the risk of recurrence, but was not an independent predictive factor for PFS and OS [11]. Woelber et al showed a similar rate of local recurrence in patients with a margin <8 mm vs. ≥8 mm (12.6% vs. 10.2% respectively) [12].…”
Section: Discussionsupporting
confidence: 89%
“…The modern concept for the treatment of advanced vulvar cancer is radical excision of the vulvar tumor and inguinofemoral lymphadenectomy, knowing that the optimal range of the free margin is 8 mm. While a microscopic margin of 2 mm seems sufficient (80% of relapses occur in patients with surgical margins less than 2 mm), less radical surgery is associated with an increased risk of relapse 7. The condition of the margins is the most important predictor of recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Although this study confirms the benefit of a more conservative approach to vulvar resection, the actual extent of the surgical margin has been controversial. Several recent studies have reported that the histopathological margin distance was not predictive of vulvar recurrence [12][13][14]18,[22][23][24][25]. However, there have been two recent exceptions, A meta-analysis of 10 studies reported by Nooij et al showed that a tumour-free margin of <8 mm was associated with a higher risk of local recurrence compared to a tumour-free margin of ≥ 8 mm (HR, 1.99; 95% CI: 1.13−3.51) [15], but in a cohort study of their own patients, they were unable to confirm this finding.…”
Section: Discussionmentioning
confidence: 99%
“…Nooij et al and Preti et al also suggested that "tumour positive margins" were the only risk factor [15,27]. Groenen et al recommended removing "no more than sufficient surrounding tissue" [12], while others have recommended that margins should be at least 2 mm [23], 5 mm [28,29] or ≥8 mm [30].…”
Section: Discussionmentioning
confidence: 99%